Analisis Pendekatan Struktural Pada Puisi “Tanah” Karya Wiji Thukul (International Forum of Researchers and Lecturers, 2023)
Poetry is the poet's interpretation of life. The interpretation reflects the poet's view of the surrounding reality. Reading poetry is a literary art enjoyment. Poetry is a rich literature that can be used to express oneself from the author, for example in Widji Thukul's poem entitled